Defaulting from antiretroviral therapy and associated factors among HIV/AIDS patients in public hospitals of Eastern Zone, Tigray, Ethiopia, 2020: a cross-sectional study - Tsegu Hailu Gebru; Haftea Hagos Mekonen (HIV & AIDS Review. International Journal of HIV-Related Problems)
Background Globally, over 76 million people have been infected with human immunodeficiency virus (HIV), and the infection has contributed to more than 35 million deaths since its emergence. Studies revealed that in developing countries, defaulting patients were outnumbering patients who were known to have died. The burden of defaulting and associated factors among adults receiving antiretroviral therapy (ART) is lacking in this particular study area. Therefore, this study aimed to assess the prevalence of defaulting and associated factors among adult HIV/AIDS patients receiving antiretroviral therapy in Eastern Zone, Tigray, Ethiopia.